Energy transfer pathways in reconstituted peridinin chlorophyll complexes - Kloz, Miroslav (Jihočeská univerzita, 2009)
The main objective of this thesis is to study energy transfer pathways between carotenoids and chlorophylls in the reconstituted light harvesting protein, peridinin chlorophyll protein (PCP), of the marine dinoflagellate Amphidinium carterae. The reconstituted PCP complex contains either bacteriochlorophyll-a or a mixture of bacteriochlorophyll-a and chlorophyll-b instead of chlorophyll-a that occurs in the native PCP. The introduction and methods of the thesis describes spectroscopic properties of carotenoids with emphasis on the carotenoid peridinin, and a brief introduction to the femtosecond pump probe spectroscopy and global fitting analysis used for treating the time resolved spectra. The main results, dependence of the peridinin to bacteriochlorophyll-a energy transfer pathways on excitation wavelength and energy transfer between chlorophylls, are described and discussed in the results of the thesis. Prohlašuji, že svoji diplomovou práci jsem vypracoval samostatně pouze s použitím pramenů a literatury uvedené v seznamu citované literatury. Prohlašuji, že v souladu s § 47b zákona č.111/1998 SB. v platném znění souhlasím se zveřejněním své diplomové práce, a to v nezkrácené podobě elektronickou cestou ve veřejně přístupné části databáze STAG provozované Jihočeskou univerzitou v Českých Budějovicích a na jejích internetových stránkách.
Energy transfer pathways in reconstituted peridinin chlorophyll complexes